Growing tilapia production and emerging sustainability issues - Singh, Atul K. (Indian Farming, 2020)
Pond, tank and cage culture of the introduced improved strains of tilapia has resulted into significantly raised aquaculture productions in India. Today, there is an emphasis on tilapia farming using cages and biofloc technology and aquaculturists are endeavouring to jump into the international market besides catering the domestic need. Looking at the prospects of developing tilapia culture, action point for further improvement of tilapia production in India are suggested for distribution of improved stocks, better formulated and floating feeds, deployment of advanced aquaculture production systems, monosex culture and continued quarantine and tighter biosecurity standards.